Pengaruh Perbandingan Tepung Okara dan Tepung Beras Terhadap Karakteristik Kue Apem - Insani, Wirda; Yusa, Ni Made; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i01.p01, 2023)
This study aimed to determine the effect of okara flour and rice flour ratio on the characteristics of apem cake and to determine the right of okara flour and rice flour to produce apem cake with the best characteristics. The experimental design used in this study was a Completely Randomized Design (CRD) with treatment that is the ratio of okara flour with rice flour which consist of 5 levels there is ( 0% : 100%; 10% : 90%; 20% : 80%; 30% : 70%; 40% : 60% ). The treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by variance test and if the treatment had a significant effect with observed parameters, it was continued with Duncan Multiple Range Test (DMRT). The result showed that the ratio of okara flour with rice flour had significant effect on water content, ash content, protein content, crude fiber content, swellability, hedonic test color, aroma, texture, taste and overall acceptance and scoring test such as color and texture. The addition 30% of okara flour with 70% rice flour ratio produces apem cake with the best characteristics with water content 38.42%, protein content 6.04%, crude fiber content 9.99%, ash content 0.71%, swellability 3.47%, the color was brown and liked, the aroma liked, the texture was soft and liked, the taste liked and the overall acceptance liked.